2020
DOI: 10.2320/matertrans.mt-m2020141
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Entropy of Exact Equiatomic High-Entropy Alloys Formed into a Single Phase

Abstract: Exact equiatomic high-entropy alloys (EE-HEAs) comprising N elements (N ² 5) formed into a single phase with either bcc, fcc or hcp structure were investigated based on sub-regular solution model. The analysis was performed by utilizing relationships among Gibbs energy (G), enthalpy (H ), entropy (S), absolute temperature (T ) and pressure (P), G = H ¹ TS and S = ¹(@G/@T ) P , for representative EE-HEAs, such as bcc-MoNbTaVW, fcc-CoCrFeMnNi and hcp-EE-HEAs comprising heavy lanthanides with and without Y. Mixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The present work led to a subsequent report about the formations of HEAs with bcc, hcp, and fcc structures simultaneously in a composition line. 8) Further relevant thermodynamic researches were performed in terms of mixing entropy of single-phase HEAs itself 9) based on CALPHAD (CALculation of PHAse Diagram) scheme to evaluate whether or not the HEAs truly possess a large magnitude of mixing entropy. These achievements with a knowledge of thermodynamics and relevant theoretical aspects assisted by computational approach have offered profound insights into the nature of HEAs.…”
Section: "Modeling and Crystal Plasticity Simulations Of Lathmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work led to a subsequent report about the formations of HEAs with bcc, hcp, and fcc structures simultaneously in a composition line. 8) Further relevant thermodynamic researches were performed in terms of mixing entropy of single-phase HEAs itself 9) based on CALPHAD (CALculation of PHAse Diagram) scheme to evaluate whether or not the HEAs truly possess a large magnitude of mixing entropy. These achievements with a knowledge of thermodynamics and relevant theoretical aspects assisted by computational approach have offered profound insights into the nature of HEAs.…”
Section: "Modeling and Crystal Plasticity Simulations Of Lathmentioning
confidence: 99%
“…Besides, Alloy C annealed at 1273 K for 200 h maintained a single-hcp structure. These achievements combined with a subsequent thermodynamic analysis of mixing entropy of single-phase HEAs itself based on CALPHAD scheme 9) will open the door for the promising fundamental researches of HEA. Silicon (Si) has attracted considerable interest as a negative electrode material for next-generation lithium (Li)ion batteries because of its high capacity density.…”
Section: "Modeling and Crystal Plasticity Simulations Of Lathmentioning
confidence: 99%
“…[43] Unfortunately, previous studies have shown that results from Thermo-Calc calculations, such as, for example, phase compositions, phase transformation temperature, and chemical compositions of phases differ to some extent from experiment results. [44][45][46] However, combining dilatometry measurements with in situ neutron diffraction data, the phase transformation type and transformation temperature of HEAs can be determined conveniently from an analysis of the length change signal from dilatometry, and the integrated peak intensity and peak position change from in situ neutron diffraction measurements. Thus, an approach using thermodynamic calculations with combined neutron diffraction and dilatometry can substantially reduce the efforts in the development of new HEA systems.…”
Section: Phase Transformation In Heasmentioning
confidence: 99%
“…36) Followed by these early studies, the present authors adopted a thermodynamic approach and calculated the value of S mix using Thermo-Calc 7,8) and a specially designated database for HEAs (TCHEA4). The present study was motivated by the authors' previous precise thermodynamic calculations, 9) indicating that S mix < S config (= S ideal ) holds for most of the exact equiatomic (EE) HEAs with a single bcc structure; in particular, for Al-containing bcc EE HEAs. Only one exception was reported, 9) for the bcc CrMoNbTaTiVZr HEA 10) at 1300 K, with S mix /S config = 1.004.…”
Section: Introductionmentioning
confidence: 99%